FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN HANDPHONE MEREK SAMSUNG DI LA CELL SANGATTA - Pasolang, Viyetri (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
Research uses quantitative methods with data collection methods using questionnaires, instrument test methods (validity and reliability), percentage deskrictive analysis, classical assumption tests, multiple regression analysis, determination analysis (R2), t test and F test using SPSS for Windows version 16. Partial test results of Income variables: That is t calculate 3,348 > t table 2,003 means a partially significant effect, variable Price: t calculate 0.265 < t table 2,003 means insignificant effect, variable Taste: t calculate 3,500 > t table 2,003 means a significant effect partially. Simultaneous test results are the value of F calculated 63,316 > F table 3.16. It can be concluded simultaneously Revenue, Price and taste influence the decision to buy Samsung brand mobile phones at LA Cell Sangatta.